O sertão e o mundo nas margens do alguidar: uma análise semiótica da canção de Chico César - Leite, Jonathan Lucas Moreira (2021)
The presented work is part of the semiotic field of studies, as well as in the studies on song. The main objective is to analyze the tensions that form the songs of Chico César, Brazilian musician, composer, and poet. Firstly, we will review the General Theory of Signs, the main framework of our study, proposed by Peirce (1975), in addition to the contributions of other authors who are guided by the Peircean perspective, such as Santaella (2000; 2004; 2005; 1997), Nöth (2003), Ferraz Júnior (2012) and Pignatari (1974). The second chapter is devoted to elucidating aspects related to music and song. We will reflect on a brief historical overview of Popular Music and its relationship with literature. We will also discuss the methodological approaches adopted for studies on popular song, focusing on the ideas systematized by Luiz Tatit. (1996; 2001; 2004). In the third chapter, we will provide a panoramic reading of the author's song, seeking to highlight the main characteristics of his work. The last chapter is about dialoguing with the concept of cultural hybridization proposed by Nestor Canclini (2019), we will reflect on the tensions between the disparate sign universes that are established in the work of the Paraibano artist, through the analysis of the songs Nato, Zabé, A prosa impúrpura do Caicó, Dança do Papangu and Folia de Príncipe.